Special education in the Commonwealth Caribbean - Miller, Errol L.
This paper describes the organization of educational services for special children in the Commonwealth Caribbean, and notes the constraining conditions affecting special education in the Caribbean. It then examines government interventions under four headings: 1) Providing trained personnel; 2) Incorporating special schools into the public system; 3) Providing special education units in primary schools; and 4) Providing related support services
Keywords: Special education